Mpox and healthcare workers - a minireview of our present knowledge - AbdulRahman A. Saied; Deepak Chandran; Sandip Chakraborty; Talha Bin Emran; Kuldeep Dhama (SpringerOpen, 2023)
Abstract Introduction Workers in the healthcare industry form the backbone of health systems everywhere. In the face of global health crises like the current monkeypox (mpox) outbreak, healthcare workers like doctors, dentists, pharmacists, nurses, midwives, paramedics, administrators, support staff, laboratory technicians, and community health workers all play crucial roles in providing care and containing the spread of the disease. Aim Therefore, in the wake of concerns about mpox recurrence, we seek to shed light on the occupational transmission of mpox infection and the possible risk to healthcare personnel. Results Contamination of the environment of the household of cases of mpox and environment of the patient care units with the viral DNA has been reported besides asymptomatic cases and detection of viral DNA in air samples; therefore, more research on non-lesion-based testing for human mpox infection for screening asymptomatic people, particularly among populations at high risk of infection, in the event of asymptomatic transmission and potential transmission via aerosols is necessary. Monitoring efforts can be aided by incorporating mpox testing into locations where people are more likely to contract illnesses and seek medical attention. We must take a precautionary infection control approach to control the spread of the virus while completing urgent research to understand better the human-to-human mpox transmission process. Conclusions In this minireview, we discuss the potential routes of mpox transmission to healthcare and preventative strategies and measures that should be taken and considered. Graphical Abstract